2021
DOI: 10.1016/j.pmedr.2021.101472
|View full text |Cite
|
Sign up to set email alerts
|

Socio-ecological correlates of physical activity in a nationally representative sample of adolescents across Ireland and Northern Ireland

Abstract: Highlights Adolescent physical activity (PA) can be categorized into different levels. Categories include inactive, somewhat active, active, or daily active. Demographic, intrapersonal and interpersonal factors varied by PA category. Depending on PA category, school- and community-related factors also varied. As Every Move Counts , future correlate analyses may benefit from PA categor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 48 publications
0
6
1
2
Order By: Relevance
“…Considering the first of the objectives, high levels of physical activity were observed in our sample of adolescents, unlike other studies that found a decrease in it at this stage of life [ 29 , 30 , 31 , 32 ]. Likewise, the HELENA study that measured the level of physical activity and time spent in a sedentary manner in adolescents from nine European countries observed, as in this research, that those who carried out moderate-to-vigorous-intensity activity had high cardiorespiratory fitness and spent less time on sedentary activities, but most adolescents spent most of their time displaying sedentary behavior [ 33 ].…”
Section: Discussioncontrasting
confidence: 89%
“…Considering the first of the objectives, high levels of physical activity were observed in our sample of adolescents, unlike other studies that found a decrease in it at this stage of life [ 29 , 30 , 31 , 32 ]. Likewise, the HELENA study that measured the level of physical activity and time spent in a sedentary manner in adolescents from nine European countries observed, as in this research, that those who carried out moderate-to-vigorous-intensity activity had high cardiorespiratory fitness and spent less time on sedentary activities, but most adolescents spent most of their time displaying sedentary behavior [ 33 ].…”
Section: Discussioncontrasting
confidence: 89%
“…Engaging in physical activity is indeed a complex behaviour affected by various elements, such as social, family-related, environmental, and peer-related influences (47,48). The social support aspects that have been most extensively researched concerning physical activity and are best suited to explain the diversity in early adolescent physical activity levels are peer pressure, family-related influence, and interpersonal support.…”
Section: Interpersonal-related: -Family Factorsmentioning
confidence: 99%
“… 1 Concerns about levels of inactivity in children and adolescents have been reported in Ireland North and South for many years, with 87 % of youth not achieving the recommended levels of PA. 2 , 3 Despite efforts to increase PA in this population, rates of physical inactivity remain high across the island of Ireland. 4 , 5 …”
Section: Introductionmentioning
confidence: 99%